2021
DOI: 10.3389/fphar.2021.682337
|View full text |Cite
|
Sign up to set email alerts
|

Development, Optimization and Evaluation of 2-Methoxy-Estradiol Loaded Nanocarrier for Prostate Cancer

Abstract: The therapeutic efficacy of antineoplastic agents possessing a selective target to the nucleus of the cancer cells could be enhanced through novel formulation approaches. Thus, toward the improvement of the anticancer potential of 2-methoxy estradiol (2 ME) on prostate cancer, the drug was entrapped into the hydrophobic micelles core formulated with Phospholipon 90G and d-α-tocopheryl polyethylene glycol succinate (TPGS). Optimization of the formulation was done by Box-Behnken statistical design using Statgrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(62 reference statements)
4
7
0
Order By: Relevance
“…This could be attributed to the increased apoptosis in the 2ME-INVA-APA treated cells. Previous studies has reported similar effect of 2ME on Bax and Bcl-2 expression (Badr-Eldin et al., 2020 ; Alhakamy et al., 2021 ). These findings substantiate 2ME-INVA-APA’s anti-neoplastic ability.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This could be attributed to the increased apoptosis in the 2ME-INVA-APA treated cells. Previous studies has reported similar effect of 2ME on Bax and Bcl-2 expression (Badr-Eldin et al., 2020 ; Alhakamy et al., 2021 ). These findings substantiate 2ME-INVA-APA’s anti-neoplastic ability.…”
Section: Discussionsupporting
confidence: 61%
“…A report deemed 2ME effective in fighting prostate cancer, although the plasma concentration of 2ME does not sustain for long (Sweeney et al., 2005 ). It was noted that a significantly high dose was required in human beings when administered orally; however, nano-2ME formulation shows enhanced pharmacokinetic properties in animal test subjects (Wang et al., 2011 ; Alhakamy et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These anti-inflammatory effect of 2ME-TPGS were more pronounced when compared with 2ME-Raw. This is consistent with Alhakamy et al [ 92 ]. The decreased expression of these inflammatory cytokines, namely TNF-α and IL-1β, has been reported to reduce apoptosis and pro-apoptotic signaling after kidney injury [ 27 , 93 ].…”
Section: Discussionsupporting
confidence: 94%